Multidisciplinary Effective Prediction of Crop using IoT and WSN (International Journal of Advanced Research in Computer Science, 2017)
In the modern world, agriculture plays a vital role in Indian economy. Agriculture gets destroyed due to fewer numbers of workers in the crop field and animal intrusions which destroys crop in the field. So, Agricultural lands are becoming plots. The main objective is to improve the sustainable agriculture by enhancing the technology using wireless sensor technology. IoT establishes a connection between the sensed values from the sensor with the internet. WSN involves two levels of prediction such as climate and crop. Temperature, Humidity and pH sensors are used to obtain the characteristic data from the land. Based on temperature and humidity, climate is predicted using fuzzy rules. From the predicted climate and using pH value of the soil, the crop to be grown is predicted. The corresponding decisions sent to the respective land ownerâ€™s. The sensors are co-ordinated using the GPS and are connected to the base station in an ad-hoc network using WLAN. Sensors are arranged in the form of master slave technique. The master systems can be connected through the WLAN so that the global crop disease warnings can be sent very easily. This system also reduces the time to be spent on the agricultural field and gives the correct suggestion at the right time, so that it helps to attain the high yield.Â Keywords: WSN, Prediction, Fuzzy Rule-base, IoT